Webquest sebagai Pembelajaran Abad 21 - Yerry Soepriyanto (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
WebQuest is a type of inquiry-oriented web-based learning by utilizing existing resources on the Internet. Bernie Dodge and Tom March created WebQuest in 1995 or the end of the twentieth century. The twenty-first century experienced rapid changes in economy and technology. These changes have an impact on the need for skills in the workplace. This article aims to discuss Webquest WebQuest which was created 23 years ago to answer the challenges of twenty-first century learning.